PENDIDIKAN AKHLAK PADA ANAK JALANAN DI SURAKARTA - Zaman, Badrus (INSPIRASI (Jurnal Kajian dan Penelitian Pendidikan Islam), 2018)
ABSTRACTThe purpose of this study was (1) To find out Moral Education in Street Children at the Seroja PPAP Surakarta Institute. (2) Knowing the Inhibiting Factors of Moral Education for Street Children in the Seroja PPAP Surakarta Institute. (3) Knowing the Drivers of Moral Education in Street Children at the Seroja PPAP Surakarta Institute. This study used a qualitative descriptive method with case study research design. The data used are primary and secondary data. Sources of data used are informants, events or activities with informant resource persons. Data collection techniques used were interviews, observation, and document analysis. The validity of the data obtained by the technique of data triangulation, triangulation of methods and review of informants. Data analysis using interactive model data analysis. Based on the results of this study, it can be concluded that: (1) Moral Education in street children in the PPO Seroja Surakarta institution uses moral model education with a non-formal education model (TPA) that is by teaching the Qur'an to read and understand the contents of the verse which is contained in the Qur'an. The counseling model is by providing assistance and supervision for street children. exemplary model that is by giving example to street children in noble character. The skill model is by teaching street children various skills for entrepreneurship. Factors that influence the difficulty of the implementation of moral education in the Surakarta Seroja PPAP institution are: street children who do not have the awareness to follow moral education, less competent staff, less supportive facilities and infrastructure, and family environments that are passive and far from noble character. The driving factor is the concern of the institution and security towards the moral education of street children, the motivation of street children who want to change for the better, and the presence of shelter houses that can be a place of refuge and can also teach various moral values and skills to street children. Tujuan penelitian ini adalah (1) Mengetahui Pendidikan Akhlak pada Anak Jalanan di Lembaga PPAP Seroja Surakarta. (2) Mengetahui Faktor Penghambat Pendidikan Akhlak Anak Jalanan di Lembaga PPAP Seroja Surakarta. (3)  Mengetahui Faktor Pendorong Pendidikan Akhlak pada Anak Jalanan di Lembaga PPAP Seroja Surakarta.Penelitian ini menggunakan metode deskriptif kualitatif dengan desain penelitian studi kasus. Data yang digunakan yakni data primer dan sekunder. Sumber data yang digunakan adalah informan, peristiwa atau aktifitas dengan nara sumber informan. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan analisis dokumen. Validitas data yang diperoleh dengan teknik trianggulasi data, trianggulasi metode dan review informan. Analisis data menggunakan analisis data model interaktif.Berdasarkan hasil penelitian ini dapat disimpulkan bahwa: (1) Pendidikan Akhlak pada anak jalanan di lembaga PPAP Seroja Surakarta menggunakan model pendidikan Akhlak dengan Model pendidikan non formal (TPA) yaitu dengan mengajarkan baca tulis al-Qur’an untuk memahami lebih lanjut isi kandungan ayat yang terdapat di dalam al-Qur’an. Model konseling yaitu dengan memberikan pendampingan dan pengawasan bagi anak jalanan. model keteladanan yaitu dengan memberi contoh kepada anak jalanan dalam berakhlak mulia. Model ketrampilan yaitu dengan mengajar anak jalanan berbagai ketrampilan untuk berwirausaha. Faktor yang mempengaruhi sulitnya penerapan pendidikan Akhlak di lembaga PPAP Seroja Surakarta yaitu: faktor anak jalanan yang belum memiliki kesadaran untuk mengikuti pendidikan Akhlak, Tentor yang kurang berkompeten, Sarana dan prasarana yang kurang mendukung, dan lingkungan keluarga yang cenderung pasif dan jauh dari akhlak mulia. Faktor pendorong yaitu kepedulian lembaga dan tentor terhadap pendidikan akhlak anak jalanan, motivasi anak jalanan yang ingin berubah menjadi lebih baik, dan adanya rumah singgah yang bisa menjadi tempat berlindung dan juga bisa mengajarkan berbagai nilai-nilai akhlak dan keterampilan kepada anak jalanan.